Maritime Awareness In Pakistan - Mr. Sohail Ahmad Azmie (CISS Insight Journal, 2017)
Pakistan has always had a sea, but it has been the most neglected area in the national policy. Owing to lack of maritime awareness, Pakistan has failed to develop its shipbuilding industry, which arguably is the driver of all other industries. A state would greatly benefit by setting up its own shipping lines, building ports, focusing on ‘blue economy’. Blue economy entails using vast sea resources, exploring ocean tides potential for renewable energy, developing coastal tourism, etc. Because of lack of maritime awareness, Pakistan has failed to capitalize on its geo-political/geo-strategic significance. Situated at the doorstep of world’s biggest energy reservoirs, Pakistan can serve as a conduit for Central Asian states access to Indian Ocean (IO) resources. Pakistani ports could have been major transhipment ports in South Asian region for China and Central Asian states. Despite being a geo-strategically important country in the region, Pakistan has failed to initiate maritime security constructs in the Arabian Sea and Indian Ocean.